ISLAMISASI ILMU EKONOMI: TAMBAL SULAM WACANA ILMIAH - Imron Mustofa (IAIN Tulungagung, 2017)
Like any other discipline, economics as a science is formed on the framework of a scientific building. It is the implementation of a particular point of view, in the sense of the product of interpretation and translation of the collaboration between the basic values ​​of the worldview and the context of all the activities that go on. Islam as a basic framework that is full of values, has its own concept of economy. In Islamic economics as an inner science context is a merger between the conceptual environment and the context of discussion, from the collaboration of these two things the economic epistemology is born. Therefore, the scheme and structure of this building acts as a scope of discussion or context of economics. On the other hand, problems begin to emerge when it intersects with the conventional economic concept of capitalism or socialism. Economics in the Islamic and conventional systems appears to be essentially tangent. Islam itself absolutely rejects all or accepts blindly. Contemporary Muslim thinkers view the economy as a creative reconceptualization, built on a collection of pre-existing thought-thinking, and always have an ever-growing bond of authority, and an evolving Islamic tradition of scholarship. Therefore, Islamization begins with an examination of the discipline of the object, by basically refining the worldview, the philosophy, and the basic values ​​of the discipline, by then eliminating points that are inconsistent with Islam and assimilating in harmony with it. Keywords: worldview, Islamization work-plan, saintific method, al-Attas, al-Faruqi.